PENGARUH PERSEPSI DAN MINAT SISWA SMA/SMK KELAS XII DI YOGYAKARTA TERHADAP PRODI D3 PENYIARAN DI AKRB YOGYAKARTA - Kusumastuti, Dwi Nurrahmi (Jurnal Ilmu Komunikasi AKRAB, 2017)
ABSTRACTFor the sophomore students in their senior high school, in choosing their majors were not an easy things to do, regarding many things should be taken as the matter of reconsideration. For example, parent?s opinion and friends, furthermore the student?s own interest and perception toward desired concentration. Interest, in the Indonesia dictionary means that some preferences regarding to which liking something or wanting something that suit the subjects. And perception means the responses of the subjects regarding something in the subject?s field of interest.In choosing their own education, SMK sophomores senior high school students would putting their full interest to the concentration which they chose, and also had their own perception towards it. This research would be using quantitative methods in order to obtain how much their perception and interest shall affect their willingness to continues their studies in AKRB Yogyakarta academy. The benefits of this research expected to grants valuable advices for referred concentration study in broadcasting field to enhances their qualities therefore the said academy would become the main choice for the students who sitting in the sophomore class. This research also expected to gives a contribution for sophomore students? interest in choosing their major in university.Keyword : Prception, Sophomore Students, Education.